Impact of the COVID-19 pandemic on incidence of tics in children and young people: a population-based cohort study. (March 2023) - Jack, Ruth H.; Joseph, Rebecca M.; Coupland, Carol A.C.; Hall, Charlotte L.; Hollis, Chris
Summary: Background: Since the onset of the coronavirus (COVID-19) pandemic, clinicians have reported an increase in presentations of sudden and new onset tics particularly affecting teenage girls. This population-based study aimed to describe and compare the incidence of tics in children and young people in primary care before and during the COVID-19 pandemic in England. Methods: We used information from the UK Clinical Practice Research Datalink (CPRD) Aurum dataset and included males and females aged 4–11 years and 12–18 years between Jan 1, 2015, and Dec 31, 2021. We grouped the pre-pandemic period (2015–2019) and presented the pandemic years (2020, 2021) separately. We described the characteristics of children and young people with a first record of a motor or vocal tic in each time period. Incidence rates of tics by age-sex groups in 2015–2019, 2020, and 2021 were calculated. Negative binomial regression models were used to calculate incidence rate ratios. Findings: We included 3, 867, 709 males and females aged 4–18 years. Over 14, 734, 062 person-years of follow-up, 11, 245 people had a first tic record during the whole study period. The characteristics of people with tics differed over time, with the proportion of females aged 12–18 years and the proportion with mental health conditions including anxiety increasing during the pandemic. Tic incidence rates per 10, 000 person-years were highest for 4–11-year-old males in all three time periods (13.4 [95% confidence interval 13.0–13.8] in 2015–2019; 13.2 [12.3–14.1] in 2020; 15.1 [14.1–16.1] in 2021) but increased markedly during the pandemic in 12–18-year-old females, from 2.5 (2.3–2.7) in 2015–2019, to 10.3 (9.5–11.3) in 2020 and 13.1 (12.1–14.1) in 2021. There were smaller increases in incidence rates in 12–18-year-old males (4.6 [4.4–4.9] in 2015–2019; 4.7 [4.1–5.3] in 2020; 6.2 [5.5–6.9] in 2021) and 4–11-year-old females (4.9 [4.7–5.2] in 2015–2019; 5.7 [5.1–6.4] in 2020; 7.6 [6.9–8.3] in 2021). Incidence rate ratios comparing 2020 and 2021 with 2015–2019 were highest in the 12–18-year-old female subgroup (4.2 [3.6–4.8] in 2020; 5.3 [4.7–6.0] in 2021). Interpretation: The incidence of tics in children and young people increased across all age and sex groups during the COVID-19 pandemic, with a differentially large effect in teenage girls (a greater than four-fold increase). Furthermore, in those with tic symptoms, proportions with mental health disorders including anxiety increased during the pandemic. Further research is required on the social and contextual factors underpinning this rise in onset of tics in teenage girls. Funding: National Institute for Health Research Nottingham Biomedical Research Centre .